First record of the genus Euepedanus from China, with the description of a new species (Opiliones: Laniatores: Epedanidae) - Zhu, Ming-Sheng; Lian, Wei-Guang (Zootaxa, 2006)
The opilionid genus Euepedanus is recorded for the first time from China and a new species, named E. flavimaculatus sp. n., is described and illustrated from specimens collected in the Diaoluo Nature Reserve on Hainan Island, China.